In vitro antioxidant potential of Ethanolic extract of Hypericum hookerianum and its Glycosidic Flavonoid enriched extract - Suba Kanmani; Murugan S; Umadevi P (International Journal of Phytomedicine, 2014)
Hypericum hookerianum in current scenario have been targeted for the treatment of neurodegenerative diseases. This study was undertaken to assess the in vitro antioxidant potential of ethanolic extract of H.hookerianum and its glycosidic flavonoid enriched extract. Dried aerial parts of H.hookerianum were extracted with ethanol using soxhlet apparatus. Glycosidic flavonoid enriched extract (GFHH) was separated by acid hydrolysis from ethanolic extract of H.hookerianum (EEHH) and performed thin layer chromatography (TLC). Total flavonoid content was determined spectrophotometrically in EEHH and GFHH. In vitro antioxidant potential of EEHH and GFHH were evaluated by various free radical scavenging methods like 1,1-Diphenyl- 2-picrylhydrazyl (DPPH), 2, 2’-azino bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS), Super oxide (O2.-), Nitric oxide(NO), 2,2-azo bis (2- amidino propane) di hydro chloride (AAPH), hydroxyl radicals (OH.) assays and compared with standard quercetin. Flavonoids (quercetin and rutin) present in the plant extracts was confirmed by TLC. Total flavonoid content (TFC) was quantified in both the extracts and the concentration of flavonoid was high in GFHH when compared with EEHH extract. In DPPH assay IC 50 values for EEHH and GFHH were 23.03 µg/ml ±0.21 and 26.45 µg/ml ±0.42 respectively. EEHH and GFHH exhibited potent scavenging effects against ABTS with an IC50 values of 8.68±0.65 μg /ml and 7.38±0.72 μg / ml which are comparatively equivalent to that of standard quercetin IC50 ( 7.17 ±0.76 μg / ml). In SO assay, IC50 values for EEHH and GFHH was found to that 48.42 µg/ml ±0.45 and 29.48 µg/ml ±0.45 respectively, in NO scavenging assay IC 50 values for EEHH and GFHH were 7.75 µg/ml ±0.45 and 7.3 µg/ml ±0.21 respectively, in AAPH assay IC 50 values for EEHH and GFHH were 8.002 µg/ml ± 0.45 and 7.3 µg/ml ±0.21 respectively, in HRSA assay IC50 values for EEHH, GFHH and standard were 17.17 ± 0.82 μg/ ml, 15.18 ± 0.92 μg/ ml and 12.17 μg/ ml respectively. In all in vitro assays, the potential of the radical scavenging is as follows: EEHH < GFHH < quercetin. Results obtained in the present study have confirmed the antioxidant potential of EEHH and GFHH due to its flavonoidal constituent. These findings support the use of H.hookerianum in traditional medicine for treating neurodegenerative diseases and oxidative stress.